A Transcription Activator-Like Effector Tal7 of Xanthomonas oryzae pv. oryzicola Activates Rice Gene Os09g29100 to Suppress Rice Immunity - Lulu Cai (Nature Portfolio, 2017)
Abstract Xanthomonas oryzae pv. oryzicola (Xoc) and X. oryzae pv. oryzae (Xoo) cause bacterial leaf streak (BLS) and bacterial leaf blight (BLB) in rice, respectively. Unlike Xoo, endogenous avirulence-resistance (avr-R) gene interactions have not been identified in the Xoc-rice pathosystem; however, both pathogens possess transcription activator-like effectors (TALEs) that are known to modulate R or S genes in rice. The transfer of individual tal genes from Xoc RS105 (hypervirulent) into Xoc YNB0-17 (hypovirulent) led to the identification of tal7, which suppressed avrXa7-Xa7 mediated defense in rice containing an Xa7 R gene. Mobility shift and microscale thermophoresis assays showed that Tal7 bound two EBE sites in the promoters of two rice genes, Os09g29100 and Os12g42970, which encode predicted Cyclin-D4-1 and GATA zinc finger family protein, respectively. Assays using designer TALEs and a TALE-free strain of Xoo revealed that Os09g29100 was the biologically relevant target of Tal7. Tal7 activates the expression of rice gene Os09g29100 that suppresses avrXa7-Xa7 mediated defense in Rice. TALEN editing of the Tal7-binding site in the Os09g29100 gene promoter further enhanced resistance to the pathogen Xoc RS105. The suppression of effector-trigger immunity (ETI) is a phenomenon that may contribute to the scarcity of BLS resistant cultivars.